Political Crisis: Conflict Between The Types Of Dimensions Of The Political - Martynyak, Yuliya (European Scientific Journal, ESJ, 2016)
In recent years, political crisis has aggravated especially in postSoviet countries. One of the most important tasks in curbing this situation is by finding the appropriate tools for describing and explaining it. The main aim of this paper is to provide an approach to the political crisis in the light of the coexistence of different types of dimensions of the political. The methodological base of research in this context is the post-marxist theory of rupture (S. Zizek, A.Badiou A., J. Ahambnen), hegemony (A. Gramsci) and ahonizm (C. Mouffe), sociology of everyday life and frame analysis, discourse analysis, and the theory of linguistic determinism. In general, this analysis focuses on anthropological dimension (near the spatial and temporal). This is especially based on the the political subjectification, which forms three basic types of correlation of the political. Every type of correlation forms the symbolic and semantic field simultaneously. Thus, such an approach expands the model of interpretation of the political crisis. In addition, it also expands the political phenomenon particularly. It can be interpreted as a multivariance in the context of three types of dimensions of the political.